2019
DOI: 10.1016/j.joca.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy identifies differences in ochronotic and non-ochronotic cartilage; a potential novel technique for monitoring ochronosis

Abstract: Objective: Alkaptonuria (AKU) is a rare, inherited disorder of tyrosine metabolism, where patients are unable to breakdown homogentisic acid (HGA), which increases systemically over time. It presents with a clinical triad of features; HGA in urine, ochronosis of collagenous tissues, and the subsequent ochronotic arthritis of these tissues. In recent years the advance in the understanding of the disease and the potential treatment of the disorder looks promising with the data on the efficacy of nitisinone. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Ochronotic samples were highly fluorescent and, unlike non‐ochronotic samples, provided limited to no discernible Raman spectral peaks. A novel peak was obtained from the ochronotic sample that was also observed in the spectra from pigment derived from synthetic HGA . The ability of Raman spectroscopy to clearly distinguish between ochronotic and non‐ochronotic tissue warrants further study, as the technique appears to have potential to provide fundamental information on the chemical nature of OP.…”
Section: Structure Of Opmentioning
confidence: 92%
See 2 more Smart Citations
“…Ochronotic samples were highly fluorescent and, unlike non‐ochronotic samples, provided limited to no discernible Raman spectral peaks. A novel peak was obtained from the ochronotic sample that was also observed in the spectra from pigment derived from synthetic HGA . The ability of Raman spectroscopy to clearly distinguish between ochronotic and non‐ochronotic tissue warrants further study, as the technique appears to have potential to provide fundamental information on the chemical nature of OP.…”
Section: Structure Of Opmentioning
confidence: 92%
“…The ability of Raman spectroscopy to clearly distinguish between ochronotic and non‐ochronotic tissue warrants further study, as the technique appears to have potential to provide fundamental information on the chemical nature of OP. Furthermore, there is potential for the technique to be employed as an in vivo tool for measuring and monitoring ochronosis progression in a clinical setting …”
Section: Structure Of Opmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectra provide the overall chemical measurement of a given sample, based on the energy exchange between the incident laser and energy used when the molecular bonds in a sample vibrate. In a study comparing non-ochronotic and ochronotic cartilage from hips and knees two main differences were found [ 120 ]. Specifically, non-ochronotic cartilage resulted in spectra comparable with that in the cartilage literature [ 121 , 122 ], whereas the pigmented cartilage was highly fluorescent.…”
Section: Rare Forms Of Crystal Deposition Diseasesmentioning
confidence: 99%
“…Recently it has been shown that Raman spectroscopy may be a useful tool for monitoring ochronosis in vivo. The ex vivo analysis of cartilage samples from the hips and ears of individuals with AKU have shown unique cartilage spectra from those with the presence of ochronotic pigment, whilst cartilages without ochronosis demonstrated a spectra that was consistent with normal cartilages [73]. Raman has the potential to be used in vivo via transdermal analysis of cartilage, it has been used on analysing cartilage and bone samples from patients with Osetogenesis Imperfecta (OI).…”
Section: Effectiveness Of Nitisinone In Akumentioning
confidence: 99%